Lean Management Systems in Knowledge Institutions: A Case of ZCAS University: A Case of ZCAS University - Mbewe, Serah (Advances in Social Sciences Research Journal, 2019)
The modern institutions are operating in a dynamic and very competitive environment. Therefore, they are challenged to make continual improvements in the way they operate as they provide quality service to their customers [1]. The solution to this is the application of the lean management system which has been successfully in the service industry in the bid to maintain a competitive advantage [2]. This paper explores the concepts of the lean approach, as applied to a knowledge institution, ZCAS University, being a higher educational institution, in the delivery of its academic programmes on the three modes of study, namely Fulltime, Part-time and Open, Distance and eLearning (ODeL). It will further explore tacit and explicit knowledge, the lean principles of conflict resolution, communication, structures, problem-solving skills and the leadership engagement needed for the implementation of a lean management system in relation to the requirements of an educational institution while closely monitoring and maintaining the quality of delivery.